The third universal theory and the new Jamahiriyan system. . International Colloquium on Muammar Qathafi's thought "The Green Book": the third universal theory and the new Jamahiriyan system : Central University of Venezuela in Caracas 12-15 November 1981 (World Center for Studies and Researches on the Green Book)
Cover title: International Colloquium on Muammar Qathafi's Thought "The Green Book" : the third universal theory and the new Jamahiriyan system : Central University of Venezuela in Caracas 12-15 November 1981.